Molecular pathways modulated by curcumin analogue, diarylpentanoids in cancer - Paulraj, Felicia Simone; Abas, Faridah; Lajis, Nordin; Othman, Iekhsan; Naidu, Rakesh (MDPI, 2019)
While curcumin has a range of therapeutic benefits, its potent anticancer activity remains an attractive avenue for anticancer research owing to the multifactorial nature of cancer itself. The structure of curcumin has thus been used as a lead to design more potent analogues, and diarylpentanoids in particular have shown improved cytotoxicity over curcumin. Investigations of diarylpentanoids have demonstrated that these compounds exert anti-cancer effects through several signalling pathways that are associated with cancer. This review focuses on selected diarylpentanoids and highlights molecular targets that modulate key pathways involved in cancer such as NF-κB, MAPK/ERK, and STAT signalling. Future research will need to focus on drug interactions to explore potential synergistic actions of diarylpentanoids and further establish the use of diverse animal models.